Skip-beat! 02 - Nakamura, Yoshiki (Shojo beat manga., 2006)
Kyoko had almost given up on her plan for revenge, but then Sho showed up at her workplace and didn't even recognize her. Her desire for vengeance refueled, she returns to the talent agency and gets assigned to a section where she can earn points for doing anything they tell her to do. With enough points, they'll back her debut, but what will they ask her to do?